Assessment of Association between Atopic Dermatitis and Attention Deficit Hyperactivity Disorder (The Planet, 2023)
Background: The face (cheeks), neck, arms, and legs arethe main body parts affected by atopic dermatitis, howeverthe groin and axillary areas are frequently spared. Findingout how often attention deficit hyperactivity disorder is inkids with atopic dermatitis is the goal. Materials andMethods: The 116 children and adolescents (ages 4 to 18)with confirmed cases of atopic dermatitis were chosen forthe research based on the inclusion and exclusion criteria.According to the 2014 American Academy of DermatologyGuidelines, atopic dermatitis was found. The Conner RatingScale served as the foundation for the diagnosis of attentiondeficit hyperactivity disorder. The Pittsburg Sleep QualityQuestionnaire was used to evaluate the sleep issue. Results:Our Atopic dermatitis patients had hyperactivity andattention deficit problems at rates of 20.68% and 32.75%,respectively. The prevalence of hyperactivity condition was also considerably greater inindividuals who had sleep issues. The study's findings indicated that hyperactivity wasprimarily responsible for the flexors' involvement. This study also shown a link between theinvolvement of the cheeks in atopic dermatitis patients, attention deficit, and sleep issues. Conclusion: children who also have certain comorbid conditions including allergic rhinitis,allergic conjunctivitis, and asthma, particularly those brought on by atopic dermatitis, aremore likely to develop hyperactivity and attention deficit disorder in later childhood. Sleepdeprivation in kids with atopic dermatitis has been demonstrated to be one of the key causes,particularly for attention deficit.
Keywords: Atopic dermatitis; Attention-deficit hyperactivity disorder; sleep disorder